PSYCHOLOGY OF ADOLESCENCE (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Adolescent psychology refers to the unique mental health needs of adolescents (defined as individuals between 10 and 19 years of age).Many people have an idea of what traditional talk therapy looks like with adults, and they might have an idea of what play therapy looks like with young children. Adolescents are a distinct group, no longer children but not yet adults, and as such have unique needs.Working in adolescent psychology means considering the specific needs of someone whose brain has developed past the childhood stage but has not fully matured into adulthood.